RIGHTS AND OBLIGATIONS OF PARENTS AND CHILDREN IN LAW NUMBER 1 OF 1974 LEGAL PERSPECTIVE OF SAYYID MALIK MARRIAGE - Yakin, Ainul; Mashudi, Lutfi (Universitas Muhammadiyah Ponorogo, 2023)
The objectives of this research are: (1) Knowing the thoughts of Sayyid Muhammad Ibnu Alawi Al-Maliki, (2) Knowing the background of Sayyid Alawi al-Maliki's thoughts, (3) Explaining the implications of the rights and obligations of parents toward children The use of research with research bibliography (library research), and the character's thought study approach. The use of personal documents as data sources and documentation methods as data collection techniques. They use content analysis (content analysis) in the data analysis technique. The study results show that parents' rights and obligations toward children are mandatory for each parent. The implication is that Sayyid Muhammad explained how parents and children fulfill their obligations and explained the rights of parents and children, namely, (1) giving an excellent name to his son. (2) educate children with the best education. (3) placing the child in a proper place and giving halal sustenance. (4) marry off children when they are old enough, and it is also the duty of children to their parents, namely to be devoted to them.